Overview of Halal Cosmetics in a Decade: A Bibliometric Analysis - Wan Suryani; Ahmad Rafiki; Fitriani Tobing; Sutan Emir Hidayat; Irwan Mohd Subri (Universitas Islam Negeri Syarif Hidayatullah Jakar, 2024)
Non-Indexed Publication